2004
DOI: 10.1111/j.0022-202x.2004.23302.x
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-5 Mutational Analysis in an Italian Cohort of Patients with Junctional Epidermolysis Bullosa

Abstract: Junctional epidermolysis bullosa (JEB) is a rare genodermatosis characterized by dermal-epidermal separation that is caused by mutations in the genes encoding hemidesmosomal components and laminin-5, the major epithelial adhesion ligand. Here, we report on the mutational analysis of LAMA3, LAMB3, and LAMC2 genes encoding laminin-5 chains in 19 Italian patients, 11 affected with the severe Herlitz (H JEB) and eight with the mild non-Herlitz variant of JEB (non-H JEB). Eighteen mutations, seven of which were nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 41 publications
(60 reference statements)
3
42
0
1
Order By: Relevance
“…Examples of such recurrent mutations in LAMB3 include: Q1083X, detected in patients of Middle Eastern origin; Q166X and W610X, seen in patients of Japanese origin; 31insC (previously reported as 29insC); and W143X, noted in patients of Italian origin. [26][27][28][29][30][31] One recurrent mutation, R650X, has been observed in the LAMA3 gene in Pakistani patients. 32 Reports of recurrent mutations in the LAMC2 gene include R95X, observed in patients of Italian origin, and Q46X, seen in patients in the Middle East region.…”
Section: Recurrent Mutationsmentioning
confidence: 99%
“…Examples of such recurrent mutations in LAMB3 include: Q1083X, detected in patients of Middle Eastern origin; Q166X and W610X, seen in patients of Japanese origin; 31insC (previously reported as 29insC); and W143X, noted in patients of Italian origin. [26][27][28][29][30][31] One recurrent mutation, R650X, has been observed in the LAMA3 gene in Pakistani patients. 32 Reports of recurrent mutations in the LAMC2 gene include R95X, observed in patients of Italian origin, and Q46X, seen in patients in the Middle East region.…”
Section: Recurrent Mutationsmentioning
confidence: 99%
“…JEB‐H is mostly caused by premature termination codon mutations, which lead to mRNA decay and lack of protein synthesis . JEB‐nH usually results from combinations of premature termination codon (PTC) mutations with missense or splice site mutations, which allow expression of a residual amount of partially functional laminin‐332 …”
mentioning
confidence: 99%
“…A 100% childhood mortality was seen in the Australasian, Austrian, International, Italian, and Dutch JEB-H cohorts, together comprising a total of 69 patients with JEB-H, in which the oldest patient had died at the age of 10 years. [3][4][5][6][7][8] Because of the discrepancy of mortality seen in these cohorts, and those seen in the NEBR, Laimer et al 5 suggested that the long-term JEB-H survivors included in the NEBR might reflect a ''limited/restricted diagnostic validity/validation.'' Indeed, the NEBR uses merely nonmolecular diagnostic testing in combination with clinical findings to classify patients according to the 2008 classification report.…”
Section: Replymentioning
confidence: 99%